Implementasi Metode Weighted Product Untuk Seleksi Calon Instruktur Pada LKP Mandiri Computer - Neny Mulyani; Yessica Siagian (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
LKP Mandiri in selecting prospective instructors still uses the assessment system manually so that all data selection of new instructor candidates does not have a fixed weight, is still subjective and often occurs errors in the calculation process and takes a relatively long time in calculating the value of the alternative. For that in this research applied weighted product (WP) method in determining new instructor candidates because the weighted product (WP) method is a method of completion by using multiplication to connect the attribute rating, where the rating must be raised first with the weight of the attribute in question, this process is the same as the normalization process. With the WP (Weighted Product) method implemented into the decision support system in LKP Mandiri facilitates calculation in making decisions to get prospective instructors.